Dampak Strategi Promosi Digital, Kualitas Pelayanan dan Word of Mouth Terhadap Keputusan Pembelian Konsumen Studi Pada Lesehan Citra - Indriani, Feri; Muhammad Yani; Mas Oetarjo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The increasingly sophisticated development of internet technology has made it no longer strange to use the internet to market a product. Business in the culinary sector is a business that is currently developing very rapidly in Indonesia. So the market share that someone has when opening a business in the culinary sector is quite promising. However, businesses in the culinary sector will experience changes, especially in the threats that will be experienced by culinary entrepreneurs. These threats include the number of competitors that will increase, technological advances and customer demands that will continue to change. This research aims to determine the impact of digital promotional strategies, service quality and word of mouth on purchasing decisions of study consumers at Lesehan Image. This research uses quantitative methods with primary data sources and secondary data. Primary data was obtained through interview techniques and the use of procedures such as distributing questionnaires, while secondary data the researcher obtained data from several supporting literature such as previous journals which were in line with this research topic. The population in this research is consumers from Lesehan Citra who use digital media, consumers who like seafood dishes, consumers who have made more than one purchase and consumers aged 17 to 40 years. The sample in this study amounted to 96 respondents. The technique used for sampling in this research uses a non-probability sampling technique with a purposive sampling technique. The results of this research are that digital promotion strategies, service quality and word of mouth have a positive and significant effect on consumer purchasing decisions.